Meningkatkan Konsentrasi Anak Melalui Metode Eksperimen Membuat Lava Gunung Merapi - Fadia Syabina Oktaviani (Departement of Mathematics Education, 2024)
The aim of this research is to identify the effectiveness of the experimental method of creating Mount Merapi lava in improving children's concentration levels in the early stages of education. The type of research used is Classroom Action Research (CAR), which is an approach to improving classroom learning practices. The stages of the CAR cycle involve problem identification, action planning, implementation, observation, evaluation, reflection, and adjustment for the next cycle. The main tool used is an observation form, which collects data during the learning process with a checklist as a guide. CAR data analysis involves description, quantitative and qualitative analysis, and data triangulation to support learning improvement. With this approach, CAR provides important insights for enhancing classroom learning. The results of the research indicate that through the experimental method of creating Mount Merapi lava, it has been proven to enhance the concentration of 5-6 year old children. Significant improvement is observed in each concentration indicator from cycle to cycle. Starting from a concentration level of 35.75% in the pre-cycle, it increased to 55.75% in cycle I meeting I, and further increased to 64.25% in cycle I meeting II. In cycle II, there was a greater increase, with a concentration level reaching 83.75% in meeting I and 86.75% in meeting II. Additionally, there was a significant improvement in the creativity indicator, increasing to 83.3%, indicating an increase in children's creativity. This change is attributed to the direct approach in the second cycle, which garnered more interest from children in the games compared to the first cycle.